Actualization Of Child Friendly Education In The Formation Of Students' Character In Integrated Islamic Primary Schools - Kusmawati, Diyah Dwi; Wiyani, Novan Ardy; Aji, Sandra Sukmaning; masruri, Masruri (At-Tarbiyat, 2024)
This research is aimed at: (1) describing and analyzing the form of actualization of child-friendly educational values ​​in forming the character of students at the Al Madinah Integrated Islamic Elementary School, Kebumen; (2) describe and analyze the challenges faced in forming the character of students at the Al Madinah Integrated Islamic Elementary School, Kebumen; and (3) describe and analyze the impact of actualizing the value of child-friendly education in character formation at the Al Madinah Integrated Islamic Elementary School, Kebumen. This research uses a qualitative approach. Data was collected using interview, observation and documentation techniques. The data that has been collected is then analyzed using the Miles and Huberman model data analysis technique which consists of data reduction, data display and verification stages. The results of the research show that the actualization of child-friendly educational values ​​to shape the character of students at SD IT Al Madinah makes them have the ability to behave or behave religiously. This religious attitude makes students able to care for others, be polite and courteous, friendly, helpful, obedient to rules, orderly, honest, responsible, disciplined, fair, love cleanliness and non-discriminatory so that they can become friendly people. This ability arises through the actualization of child-friendly educational values ​​carried out through learning activities, habituation, developing talents and interests as well as extracurricular activities, conditioning, and providing gifts and punishments for students.